The Effect of Stirrer Depth And Electroless Coating of Hardness And Tensile Strength in Aluminium Matrix Composite AL6061-AL2O3 - Sukma Andini; Eko Surojo; Teguh Triyono (Mekanika: Majalah Ilmiah Mekanika, 2021)
Metal Matrix Composite (MMC) are composite materials that are widely used in the industrial sector. Examples of metal matrix composites are Al6061 as matrix alloys and Al2O3 as reinforcement. In general, making Al6061-Al2O3 composites using the stir casting method. This research was conducted to determine the effect of the depth of stirring and electroless coating treatment on the hardness and tensile strength of Al6061-Al2O3 composites. The process of making composites with Al2O3 reinforcing particles with 6% weight fraction mixed with aluminium alloys and 2.5% magnesium powder as a wetting agent. Variations of this study were the depth of the stirrer and electroless coating treatment. The depths of stirring used for the experiment were 30%, 45%, and 60% of the height of the fluid. The testing phases in this study were the density and porosity test, metallographic observation, hardness test, and tensile test. The most efficient variation of the mixer depth was obtained at a mixer depth of 30% of the fluid height. The highest hardness and tensile strength test results are hardness value of 72.43 Brinell Hardness (HB) and tensile strength of 182.19 MPa with electroless coating reinforcement treatment.